2021
DOI: 10.1101/2021.07.26.453851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of theta transcranial alternating current stimulation (tACS) on exploration and exploitation during uncertain decision-making

Abstract: Exploring ones surroundings may yield unexpected rewards, but is associated with uncertainty and risk. Alternatively, exploitation of certain outcomes is related to low risk, yet potentially better outcomes remain unexamined. As such, risk-taking behavior depends on perceived uncertainty and a trade-off between exploration-exploitation. Previously, it has been suggested that risk-taking may relate to theta activity in the prefrontal cortex. Furthermore, previous studies hinted at a relationship between a right… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In line with previous NIBS studies about adaptive learning (medium effect size, Cohen's d = 0.5) (Soutschek et al 2018;Wischnewski and Compen 2022), a priori power analysis conducted via G*Power 3.1.9 (Faul et al 2007) showed that 34 participants would ensure 95% statistical power. This calculation was performed on a paired t-test, with a power of 0.8 and an α = 0.05.…”
Section: Participantssupporting
confidence: 79%
See 1 more Smart Citation
“…In line with previous NIBS studies about adaptive learning (medium effect size, Cohen's d = 0.5) (Soutschek et al 2018;Wischnewski and Compen 2022), a priori power analysis conducted via G*Power 3.1.9 (Faul et al 2007) showed that 34 participants would ensure 95% statistical power. This calculation was performed on a paired t-test, with a power of 0.8 and an α = 0.05.…”
Section: Participantssupporting
confidence: 79%
“…Previous studies established links between theta frequency and uncertainty (Cavanagh et al 2012; Wischnewski and Compen 2022). For example, the increase in reaction time during a decision-making task when theta tACS was applied, has been suggested to reflect an increase in perceived uncertainty (Wischnewski and Compen 2022). Consistently, our findings further provide insight into how theta tACS may influence subjective uncertainty from a computational perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established links between theta frequency and uncertainty (Cavanagh et al 2012;Wischnewski and Compen 2022). For example, the increase in reaction time during a decision-making task when theta tACS was applied, has been suggested to reflect an increase in perceived uncertainty (Wischnewski and Compen 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 13, 2022. ; https://doi.org/10.1101/2022.06.28.497899 doi: bioRxiv preprint Cohen's d = 0.5) (Soutschek et al 2018;Wischnewski and Compen 2022), a priori power analysis conducted via G*Power 3.1.9 (Faul et al 2007) showed that 34 participants would ensure 95% statistical power. This calculation was performed on a paired t-test, with a power of 0.8 and an α = 0.05.…”
Section: Participantsmentioning
confidence: 99%